Pengaruh Word of Mouth (WOM) terhadap Minat Beli Makanan - Muhammad Yusuf; Nailul Izza; Rischa Afifatin Naswa; Jawahirul Maknuun; Didit Darmawan (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze the influence of word of mouth communication on consumer purchasing interest in the food sector. The method used is a literature study with a descriptive qualitative approach, where data is obtained from various scientific articles and relevant journals that discuss the relationship between word of mouth and consumer behavior. The results of the analysis show that word of mouth has a positive and significant influence on increasing consumer purchasing interest. Important elements of word of mouth, such as recommenders (talkers), interesting topics of conversation, information dissemination media, consumer participation, and message effectiveness, have been shown to play a major role in shaping perceptions, building trust, and driving purchasing decisions. In addition, the power of personal recommendations delivered informally is considered more credible and convincing than conventional promotions. Therefore, word of mouth strategies are an effective and cost-effective marketing tool for culinary business actors to increase consumer appeal, trust, and loyalty in a sustainable manner.